2000
DOI: 10.1021/jo0004106
|View full text |Cite
|
Sign up to set email alerts
|

Solvolyses of 2-Deoxy-α- and β-d-Glucopyranosyl 4‘-Bromoisoquinolinium Tetrafluoroborates

Abstract: The solvolyses of 2-deoxy-alpha- and beta-D-glucopyranosyl 4'-bromoisoquinolinium tetrafluoroborates (1 and 2) were monitored in aqueous methanol, ethanol, trifluoroethanol, and binary mixtures of ethanol and trifluoroethanol. The observed rate constants are consistent with the solvolyses of 1 and 2 proceeding via dissociative (D(N) A(N)) transition states. In comparison to the alpha-anomer, solvolysis of the beta-compound gives a greater transition state charge delocalization onto the ring oxygen atom. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…In subsequent work Bennet and coworkers, studying the hydrolyses of 2-deoxy glucopyranosyl pyridinium ions in the presence of added azide arrived at lifetimes of 1.4 × 10 −11 s and 2.7 × 10 −11 s for the ion pair encounter complexes originating from the β- and α-salts, respectively, and concluded that the 2-deoxyglucopyranosyl oxocarbenium ion is not fully solvent equilibrated in water (Table 7). 79,80 Extrapolating the azide clock method to the solvolysis of CMP N -acetyl neuraminate, Horenstein and Brunner determined a lifetime of ≥3 × 10 −11 s at pH 5 for the N -acetyl neuraminate oxocarbenium ion (Table 7), and concluded that the α-carboxylate stabilizes the oxocarbenium ion. 81 This latter suggestion is in agreement with Horenstein’s early computational work in which it was found that the α-carboxylate stabilizes the oxocarbenium ion electrostatically by 110 kcal.mol −1 relative to the carboxylic acid in the gas phase, but only by 17 kcal.mol −1 in water.…”
Section: Influence Of C-o Bonds and Other Substituents On The Formamentioning
confidence: 99%
“…In subsequent work Bennet and coworkers, studying the hydrolyses of 2-deoxy glucopyranosyl pyridinium ions in the presence of added azide arrived at lifetimes of 1.4 × 10 −11 s and 2.7 × 10 −11 s for the ion pair encounter complexes originating from the β- and α-salts, respectively, and concluded that the 2-deoxyglucopyranosyl oxocarbenium ion is not fully solvent equilibrated in water (Table 7). 79,80 Extrapolating the azide clock method to the solvolysis of CMP N -acetyl neuraminate, Horenstein and Brunner determined a lifetime of ≥3 × 10 −11 s at pH 5 for the N -acetyl neuraminate oxocarbenium ion (Table 7), and concluded that the α-carboxylate stabilizes the oxocarbenium ion. 81 This latter suggestion is in agreement with Horenstein’s early computational work in which it was found that the α-carboxylate stabilizes the oxocarbenium ion electrostatically by 110 kcal.mol −1 relative to the carboxylic acid in the gas phase, but only by 17 kcal.mol −1 in water.…”
Section: Influence Of C-o Bonds and Other Substituents On The Formamentioning
confidence: 99%
“…Simple sugars make up a wide variety of substances found in nature, from DNA to cellulose to biological energy storage mechanisms. Consequently, the glycosidic bond has been studied experimentally for a wide variety of compounds, [1][2][3][4][5][6][7][8][9][10][11][12][13] predominantly through hydrolysis, under a myriad of conditions, and is important in the consideration of enzymatic glycosyl-transfer reactions. One of the reasons it has been studied so extensively is because of the rich and often subtle variety of the reactions that take place.…”
Section: Introductionmentioning
confidence: 99%
“…Adding to the complexity are competing hydrolysis reactions when multiple products are possible. [1] It is accepted that the reaction proceeds through an oxocarbenium cation intermediate; the mechanism involved in hydrolysis of glucopyranosides has been concluded to be dissociative (D N +A N ) or partially-dissociative (A * N D N ) [1,2,13] which lies between S N 2 and S N 1 behavior, although a concerted mechanism (A N D N ) [5,6] has been observed for the case of aqueous hydrolysis of fluoro-a-d-glucopyranoside (see ref. [14,15] for notation details).…”
Section: Introductionmentioning
confidence: 99%
“…21 Secondary alkyl cations lacking stablizing groups such as 2-adamantyl will have shorter lifetimes; even the resonance-stabilized secondary 2-deoxyglucosyl oxacarbenium ion may not be solvent equilibrated in typical alcoholic solvolysis media. 22 Short or negligible lifetimes of cations formed during the solvolysis of unactivated secondary substrates are probably the main factor underlying a long-running controversy: 6,20 e.g. does 18 O scrambling of oxygen in 'unreacted' sulfonates indicate ion pair return on the main reaction pathway 20 or a side reaction via a concerted polar mechanism?…”
Section: Discussionmentioning
confidence: 99%